Strengthening Interaction in Islamic Education Learning Through The Use of Learning Management Systems in The Digital Era - Ahd Mujahid; Mohamad Madum (INJIES: Journal of Islamic Education Studies, 2026)
This study aims to analyze the role of Learning Management Systems (LMS) in strengthening interaction in Islamic education learning within the digital era. The research focuses on how digital learning platforms facilitate communication, collaboration, and engagement between teachers and students in the learning process. This study employed a qualitative literature review, examining relevant studies, academic articles, and educational practices related to LMS implementation in Islamic education. Data were analyzed through thematic analysis to identify patterns, opportunities, and challenges in digital learning interaction. The findings indicate that the use of LMS significantly improves learning interaction through discussion forums, online assignments, feedback mechanisms, and flexible access to learning materials. In addition, LMS supports student-centered learning and encourages active participation in Islamic education classes. However, several challenges remain, including digital literacy gaps, limitations in technological infrastructure, and varying levels of teacher readiness. The study concludes that LMSs serve as effective digital learning platforms for enhancing interaction in Islamic education and recommends strengthening technological competence and institutional support to maximize learning outcomes in the digital era